Puta: reflexões sobre um processo de criação em dança a partir do diálogo entre ballet clássico e pensamentos contemporâneos em dança - AMARANTE, Alice Cáritas Almeida (2021)
The present research has as general objective to reflect about the process of creation of the PUTA solo, as proponent of dialogues between the processes of creation in classical ballet and contemporary thoughts in dance. Using for instruments of analysis, both the personal trajectory of the author and the acting of transgressors in the historical way of ballet. In order to deal with creation processes, this paper brings to discussion, mainly, the thoughts of Cecília Salles and Fayga Ostrower, assuming that processes are transitories, without determined finals and beginnings and have it constitutions based on sensible. With the view to dialogue with “contemporary thoughts”, this research has as, predominant, theoretical bases, ideas of Thereza Rocha and Laurence Louppe, referring to the intention of which contemporary thoughts are born of the reflections to which we are submitted in the internal and external relations to us. The research has an autobiographical qualitative basis, having as instruments the images, reports, observations on the theme that surrounds the author, as an artist and teacher of dance. With the conclusion of this research, it is verified that "contemporary dance" can be inserted in any work of any dance genre, that seeks to look at the world, to social relations, in a sensible way and proposing analyzes and changes regarding situations that deserve to be put in schedule of discussions and possible reforms. This research is an invitation to reflection on dance, specifically to classical ballet, in contemporary times.